Calidad de vida relacionada con la salud oral en adultos de la ciudad de Macas, Ecuador, 2021 - Molina-Merino, Jefferson Israel (2021)
Objective: To determine the quality of life related to oral health in 18-99-year-old people in the city of Macas-Ecuador 2021. Materials and methods: This was a descriptive, cross-sectional study following a quantitative approach. A total of 415 people over 18 years of age from Macas-Ecuador were evaluated. The instrument of measure was a OHIP-14 instrument composed of 7 dimensions, each of which had 2 questions. The study variables (sex, age, socioeconomic level, occupation) were analyzed using the Mann-Whitney U statistical test, with p <0.05 being considered as significant. Results: There was a predominance of 63% of women. The dimension of “psychological distress” had the highest overall impact of all the items answered. Comparison of the OHIP-14 dimensional scores between men and women showed statistically significant differences in functional limitation and handicap with p = 0.012 and p = 0.036, respectively. Conclusions: There is a relationship between quality of life and oral health among the inhabitants of the city of Macas-Ecuador. The OHIP-14 instrument showed the dimension of “psychological distress” to be the main factor of oral problems.